Investigation of the Environmental Stability of Poly(vinyl alcohol)–KOH Polymer Electrolytes for Flexible Zinc–Air Batteries - Fan, Xiayue; Liu, Jie; Ding, Jia; Deng, Yida; Han, Xiaopeng; Hu, Wenbin; Zhong, Cheng (Frontiers in Chemistry, 2019)
Next-generation wearable and portable electronic devices require the development of flexible energy-storage devices with high energy density and low cost. Over the past few decades, flexible zinc–air batteries (FZABs), characterized by their extremely high theoretical energy density from consuming oxygen in air and low cost, have been regarded as one of the most promising power supplies. However, their unique half-open structure poses great challenges for the environmental stability of their components, including the electrolyte and electrodes. As an important ionic conductor, the poly(vinyl alcohol) (PVA)–KOH gel polymer electrolyte (GPE) has been widely utilized in FZABs. To date, most studies have focused on investigations of the electrode, electrocatalyst materials and battery configuration, while very few have paid attention to the influence of the environment on the electrolyte and the corresponding FZAB performance. Herein, for the first time, the environmental stability of PVA–KOH GPE, such as dimensional stability and water and ionic conductivity retention capability, for FZABs in ambient air has been thoroughly studied. Moreover, the properties of the assembled FZABs in terms of cycling stability, discharge performance and power output are investigated. This report aims to play a leading role in examining the environmental stability of electrolytes in FZABs, which is critical for their practical applications.